Perbandingan Karakteristik Morfologi Talus Rumput Laut Kappaphycus alvarezii Pasca Transportasi Jarak Jauh - Suhardi B Basyir; Welem Linggi Turupadang (Jurnal Aquatik, 2026)
This study aims to analyze the comparison of morphological characteristics of the thallus of seaweed Kappaphycus alvarezii after long-distance transportation. Seaweed seed transportation is an essential stage in the aquaculture supply chain, but environmental conditions during travel can affect the quality and viability of the seedlings. This study examines changes in thallus morphology as a primary indicator to assess the quality and health of seedlings after the distribution process. The results showed that seedlings transported under controlled conditions had fresher, more elastic thalli with more branches compared to those under uncontrolled transport. Thallus morphology proved to be an effective indicator in assessing the physiological condition of seedlings after long-distance transportation. These findings are crucial for developing an efficient and sustainable seaweed seed distribution system. Keywords: Kappaphycus alvarezii, seedling quality, long-distance transport, thallus morphology, seaweed.